Continuous energy recovery and nutrients removal from molasses wastewater by synergistic system of dark fermentation and algal culture under various fermentation types. (March 2018) - Ren, Hong-Yu; Kong, Fanying; Ma, Jun; Zhao, Lei; Xie, Guo-Jun; Xing, Defeng; Guo, Wan-Qian; Liu, Bing-Feng; Ren, Nan-Qi
Highlights: Molasses wastewater was treated by continuous dark fermentation and algal culture. Effect of fermentation type on energy recovery and nutrients removal were studied. Butyrate-type fermentation was the most suitable fermentation type. Synergistic system produced 97.3% additional energy than dark fermentation alone. The nutrients removal efficiencies were over 85% in continuous operation. Abstract: Synergistic system of dark fermentation and algal culture was initially operated at batch mode to investigate the energy production and nutrients removal from molasses wastewater in butyrate-type, ethanol-type and propionate-type fermentations. Butyrate-type fermentation was the most appropriate fermentation type for the synergistic system and exhibited the accumulative hydrogen volume of 658.3 mL L −1 and hydrogen yield of 131.7 mL g −1 COD. By-products from dark fermentation (mainly acetate and butyrate) were further used to cultivate oleaginous microalgae. The maximum algal biomass and lipid content reached 1.01 g L −1 and 38.5%, respectively. In continuous operation, the synergistic system was stable and efficient, and energy production increased from 8.77 kJ L −1 d −1 (dark fermentation) to 17.3 kJ L −1 d −1 (synergistic system). Total COD, TN and TP removal efficiencies in the synergistic system reached 91.1%, 89.1% and 85.7%, respectively. This study shows the potential of the synergistic system in energy recovery and wastewater treatment.